Determination of Residues of Triclopyr in Fishes of Caspian Sea (Iran) - EBADI, A.G. (Asian Journal of Chemistry, 2010)
In this paper, the remains of chloride organochlorine insecticide sprays such as triclopyr(2,4,5-T), in the four the most consumed kinds of fishes found in Caspian sea were investigated. Four different kinds of fishes (Sefid, Koli, Kilca and Kafal fish) were selected. 100 Samples of fishes were collected from four different hunting regions (Chalous, Babolsar city, Khazar Abad and Miankaleh) in 2004. After cleaning, Hun muscle of the samples were prepared, then after the process of extraction, the fishes were distilled in vacuum by means of organic solvent. The results of insecticides analyzed in four kinds of fishes showed that Kafal in the hunting region of Khazar Abad had greatest amount of 0.037 ppm. Kilca from Chalous had the highest amount of triclopyr(2,4,5-T), 0.029 ppm (p < 0.05). In case of Sefid and Koli fishes, significant difference was not seen. It is nesserary to mention that no research has so far been done to be a criterion for comparison in this area, But, fortunately the amounts of the insecticide sprays has not reached to standard level in fishes and it raises the alarm health.